2013
DOI: 10.3168/jds.2013-7108
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority trial on the efficacy of premilking teat disinfectant against naturally occurring new intramammary infections using a novel 2-step diagnostic process

Abstract: The objective of the study was to evaluate premilking teat disinfectant efficacy with the use of a novel diagnostic protocol against a positive control. The evaluation of efficacy was based on establishing noninferiority of a new premilking teat disinfectant compared with an existing premilking teat disinfectant. Approximately 200 cows were randomly allocated to 1 of 2 groups. Study personnel were blinded as to cow allocation and identification of the premilking disinfectants. Quarters were disinfected using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 21 publications
(39 reference statements)
1
23
0
1
Order By: Relevance
“…(), Ceballos‐Marquez et al . () and Godden et al . () showed that the bacteriological status of their herds was determined by collecting milk samples before the commencement of the study.…”
Section: In Vivo Testingmentioning
confidence: 87%
See 2 more Smart Citations
“…(), Ceballos‐Marquez et al . () and Godden et al . () showed that the bacteriological status of their herds was determined by collecting milk samples before the commencement of the study.…”
Section: In Vivo Testingmentioning
confidence: 87%
“…() collecting a monthly sample, whereas Ceballos‐Marquez et al . () collected milk samples biweekly but only cultured them depending on SCC analysis.…”
Section: In Vivo Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine is crucial to human health both as an essential dietary element necessary for proper thyroid function (WHO ) and as a germicide important in the reduction of bacterial populations, particularly as pre‐ or post‐milking teat disinfectant (Galton ; Ceballos‐Marquez and others ). Although iodine deficiency poses health risks and remains problematic in many parts of the world, over‐dosage of iodine is also associated with health risks, such as toxic goiter, hyper‐thyroidism, and hypo‐thyroidism (Delange and others ; WHO ; Medici and others ; Sun and others ; Shi and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments to existing protocols have been proposed to test the noninferiority of an experimental product compared with a control product, based on adequate statistical approaches and reasonable logistical modifications (Ceballos-Marquez et al, 2013).…”
mentioning
confidence: 99%